Compact Dual-Channel (Hyperspectral and Video) Endoscopy - Cai, Fuhong; Gao, Min; Li, Jingwei; Lu, Wen; Wu, Chengde (Frontiers in Physics, 2020)
Combining reflected endoscopic image with spectral data has recently attracted much attention. We use optical fiber bundle probe, galvo-scanning module and imaging spectrometer module to realize a dual-channel endoscope capable of simultaneous acquisition of real-time video data and high throughput hyperspectral data. The frame per second of the video channel is 30, and the wavelength range in the hyperspectral channel is 400 - 750 nm, with 3 nm spectral resolution at 547 nm. To achieve fast hyperspectral imaging, we extract the region of interest (ROI) area from the video channel and utilize it as guidance to drive the galvo-scanning module to obtain the hyperspectral data in the ROI. In this way, the hyperspectral imaging speed for a selected ROI area can be reduced to less than 1 second, making it possible to achieve rapid detection. Utilizing this system, we acquired the hyperspectral image of fingerprints, dorsum of hand and skin melanin nevus, all of which demonstrate the compact dual-channel endoscopy has broad implications for research and therapeutics.